2003
DOI: 10.1046/j.1468-1331.2003.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalography in stroke: a 1‐year follow‐up study

Abstract: Recovery after stroke is closely linked to cerebral plasticity. Magnetoencephalography (MEG) is a non-invasive technique, which allows location of cerebral cells activities. In the present work, a cohort of patients has been studied with MEG. Twelve patients with a recent ischemic or hemorragic stroke were included as soon as possible after onset of stroke. Neurologic assessment, including standard neurologic examination, functional independence measure (FIM) and Orgogozo's scale was performed for 1 year in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 39 publications
(70 reference statements)
0
16
1
Order By: Relevance
“…The amplitude of the early SI response has been shown to correlate with tactile discrimination ability [Knecht et al, 1996;Wikstrom et al, 2000], whereas association of SI activation strength with other functional outcome measures has been more variable [Gallien et al, 2003;Tecchio et al, 2006]. In the present study, no correlation between SI strength and motor recovery was observed at acute phase or during recovery.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The amplitude of the early SI response has been shown to correlate with tactile discrimination ability [Knecht et al, 1996;Wikstrom et al, 2000], whereas association of SI activation strength with other functional outcome measures has been more variable [Gallien et al, 2003;Tecchio et al, 2006]. In the present study, no correlation between SI strength and motor recovery was observed at acute phase or during recovery.…”
Section: Discussioncontrasting
confidence: 60%
“…Changes in somatosensory activation have been less extensively studied, but previous reports have shown that interhemispheric differences in the locations and latencies of the primary somatosensory (SI) cortex activation are associated with functional recovery of stroke patients [Gallien et al, 2003;Rossini et al, 1998;Tecchio et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…First, in the early post-stroke phase, the cortical activity in response to somatosensory input predicts late motor outcomes (Zeman & Yiannikas, 1989). Absence of cortical activation by sensory stimulation is associated with poorer outcome in stroke patients (Gallien et al, 2003), while the increased activation of MI and SI by somatosensory stimulation correlates with improvements in neurological scores between the acute and chronic stages of illness (Huang et al, 2004); moreover, the degree of improvement in hand function correlates with the activation peak changes within the ipsilesional SI (Laible et al, 2012). On the other hand, in patients with poorer recovery, movements of the paretic limb are associated with a compensatory recruitment of parallel sensorimotor networks, including the bilateral dorsolateral PM, SMA, cingulate motor areas, and parietal cortices (Ward & Cohen, 2004).…”
Section: The Role Of Sensory Function In Motor Recoverymentioning
confidence: 99%
“…Changes in cortical activity during active and passive movements and motor imagery in both normal subjects and stroke patients have been variously investigated using such different techniques as functional magnetic resonance imaging (fMRI) [8-13], positron emission tomography (PET) [14,15], magnetoencephalography (MEG) [16,17], near-infrared spectroscopy (NIRS) [18] and electroencephalography (EEG) [19]. Studies exploring the therapeutic utility of EEG have reported modulation in cortical activations during motor execution and imagery practices.…”
Section: Introductionmentioning
confidence: 99%